Augmented Reading - Texeira, João Marcelo X N; Souza, Júlia D T De (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
Reading is one of the basic activities inherent to humans. By reading, we communicate to each other, sharing and receiving information. In a world technology is constantly evolving, it is not hard to find software solutions for speed reading. However, the true benefit of some of those solutions is still unclear. In this work, we verify the viability of implementing AR-based speed reading solutions, so that one may use them with real books, instead of digital ones. We implement an AR equivalent of two well-known solutions, Bionic Reading and Spritz, show the perceived limitations and confirm that AR can also try to improve reading tasks.